Severe mixed mitral valve disease due to massive mitral annular calcification — a case report and literature review - Fateh Ali Tipoo Sultan; Sheema Saadia (Journal of the Pakistan Medical Association, 2022)
We present an unusual case of massive mitral annular calcification (MAC) leading to severe mixed mitral valve disease viz: severe mitral regurgitation and severe mitral stenosis. To our knowledge severe mixed mitral valve disease secondary to MAC is extremely rare. The patient presented with worsening shortness of breath and signs of congestive heart failure. Echocardiographic examination revealed massive mitral annular calcification. Despite the massive annular calcification, she had experienced neither embolism nor endocarditis in the past. Because of severe symptomatic mitral regurgitation and mitral stenosis, surgery was advised, however the patient declined. Continuous...